2006
DOI: 10.1111/j.1600-079x.2006.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotective effect of melatonin against cisplatin‐induced testicular toxicity in rats

Abstract: In this study, we investigated the effect of melatonin on cisplatin-induced spermiotoxicity using quantitative, biochemical and histopathological approaches. Cisplatin (CP, 7 mg/kg) and melatonin (10 mg/kg) were intraperitoneally injected. The rats were decapitated on 5th (short-term group) or 50th day (long-term group) after CP injection. Traits of reproductive organs, sperm characteristics, testicular histological findings, and the lipid peroxidation in the testicular tissue were determined. Melatonin mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
137
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(163 citation statements)
references
References 35 publications
19
137
3
4
Order By: Relevance
“…It has also been reported that co-administration of speman with cisplatin showed significant improvement on the sperm quantity and quality along with enhanced steroidogenesis in mice (Sainath et al, 2011). In fact the use of another antioxidant, i.e., melatonin in combination with cisplatin has also shown chemoprotective effect against cisplatin-induced testicular toxicity in rats (Atessahin et al, 2006) which also supports the present findings.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It has also been reported that co-administration of speman with cisplatin showed significant improvement on the sperm quantity and quality along with enhanced steroidogenesis in mice (Sainath et al, 2011). In fact the use of another antioxidant, i.e., melatonin in combination with cisplatin has also shown chemoprotective effect against cisplatin-induced testicular toxicity in rats (Atessahin et al, 2006) which also supports the present findings.…”
Section: Discussionsupporting
confidence: 80%
“…Anticancer drugs/chemicals induce sperm abnormalities indicating its genotoxicity to germ cells (Wyrobek et al, 1983;Seetharama Rao and Narayana, 2005;Atessahin et al, 2006). Cisplatin has been considered as a potent mutagen causing formation of abnormal male germ cells (Sawhney et al, 2005;Mohammadnejad et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…17,[26][27][28] One of its most frequent and serious side effects is nephrotoxicity, which is described as acute tubular necrosis (ATN). Although the mechanisms of CP-induced nephrotoxicity are not fully understood, one mechanism of this toxicity is believed to involve ROS generation and inflammatory machine in the pathophysiology of CP-induced ATN after even a single dose of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…This evolutionarily conserved compound has been shown to reduce oxidative stress in the testes induced by ethanol, 167 indomethacin, 168 X-irradiation, 169 streptozotocin-induced diabetes, 86 and cisplatin. 136 In vitro studies have also shown that melatonin and its immediate precursor N-acetyl-serotonin could inhibit ascorbate-Fe (II) induced lipid peroxidation in rat testicular microsomes and mitochondria. 170,171 The administration of antioxidants such as resveratrol, ascorbate or cocoa rich in flavanols to normal animals, not suffering from induced oxidative stress, also appears to improve testicular function, suggesting that oxidative stress is a consistent feature of testicular physiology.…”
Section: Disruption Of the Antioxidant Status Of The Testesmentioning
confidence: 99%